An Analysis of Mathematical Problem Solving Ability in Terms of Students’ Cognitive Style in Learning PBL Includes Ethnomatematics (Universitas Negeri Semarang, 2019)
This study aims to (1) analyze the students’ mathematics problem solving ability with cognitive style in learning PBL which contains Ethnomathematics; (2) analyze the students’ mathematics problem solving ability with cognitive style viewed from gender defferentiation. Type of the research is descriptive qualitative research. The data was taken from Group Embedded Figure Test (GEFT). The subjects of this research were given introduction of Polya problem solving steps and Problem Solving Test (TPM). The students’ answers in TPM were analyzed and the research subjects were interviewed as triangulation. The result of this research showed that (1) Field Dependent man (FDLk) subjects could write detected and questioned matters, not clear enough in making problem sketch, could not finish the problems in all Polya steps. Field Dependent woman (FDPr) subjects could write detected and questioned matters, could arrange the completion planning, could not implement the completion planning and recheck the result of completion; (2) Field Intermediate man (FDILk) and Field Intermediate woman (FDIPr) subjects could not be carefully and only could finish three of four steps in Polya problem solving; (3) Field Independence man (FILk) and Field Independence woman (FIPr) could finish all Polya steps. Teachers should be able to create learning activities that are adjusted to the students’ cognitive styles, correct preriquisite knowledge, give counting skill, and give open-ended questions so the students have good problem solving abilities. Keywords: Cognitive Style, Problem Solving Ability, Problem Solving